Kesejahteraan Spiritual Berkorelasi dengan Kualitas Hidup Pasien Stroke - Setya Putri, Devi; Azahro, Linda Nur Maulinda; Nur, Hirza Ainin; Wulan, Emma Setiyo; Cahyanti, Luluk; Purwandari, Nila Putri (Journal Keperawatan, 2024)
Background: Stroke is still one of the major health problems, not only in Indonesia but in the world. A person who experiences a stroke will affect several aspects such as physical, psychological, social and spiritual health aspects. Stroke does not only involve neurological aspects but has an impact on the crisis of belief in God the giver of strength, the meaning of life he experiences and hope. The attack in stroke patients occurs suddenly, causing changes and more complex problems. So that spirituality becomes very important to improve the quality of life. Purpose: This study aims to analyze the relationship of spiritual well-being to quality of life in stroke patients at RA Kartini Jepara Hospital. Methods: This type of research is quantitative correlational, using crossectional research design, sampling technique with total sampling, and data collection using SWBS and WHOQOL-BREF instruments. Results: The results of the study of 34 respondents found as many as 30 respondents (88.2%) had high spiritual well-being and as many as 21 respondents (61.8%) had a very good quality of life. Based on the results of the spearman rank test, a significance number (p value) of 0.001 <0.01 was obtained so that Ha was accepted and H0 was rejected. Conclusion: There is a significant relationship between spiritual well-being and the quality of life of stroke patients at RA Kartini Jepara Hospital.